PHENOMENON OF INTERFERENCE IN TEACHING FRENCH AS A SECOND FOREIGN LANGUAGE AT THE MEDICAL UNIVERSITY (ON THE EXAMPLE OF THE COURSE "FRENCH (THE SECOND FOREIGN LANGUAGE)") - Лашків, Т. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the interference peculiarities of the native language and the English language at the phonetic, syntactic, lexical-semantic and spelling levels of French taught as a second foreign language.